2022
DOI: 10.2196/29384
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Cognitive Behavioral Therapy for Generalized Anxiety Disorder in Nationwide Routine Care: Effectiveness Study

Abstract: Background Therapist-supported, internet-delivered cognitive behavioral therapy (iCBT) is efficacious for generalized anxiety disorder (GAD), but few studies are yet to report its effectiveness in routine care. Objective In this study, we aim to examine whether a new 12-session iCBT program for GAD is effective in nationwide routine care. Methods We administered a specialized, clinic-delivered, therapist-sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…This effect is comparable to those reported in meta-analytic reviews on iCBT for GAD ( g = 0.79, Eilert et al, 2021 ) and even traditional CBT ( g = 0.84; Cuijpers et al, 2014 ). Also, similar to other iCBT trials (e.g., Ritola et al, 2022 ), effect size seemed to be affected by adherence: Patients with at least 4 of altogether 12 completed modules had an even bigger effect size ( d = 1.24). The robustness of the effect is supported by the effects on worry ( d = 0.47) and anxiety ( d = 0.38).…”
Section: Discussionsupporting
confidence: 73%
“…This effect is comparable to those reported in meta-analytic reviews on iCBT for GAD ( g = 0.79, Eilert et al, 2021 ) and even traditional CBT ( g = 0.84; Cuijpers et al, 2014 ). Also, similar to other iCBT trials (e.g., Ritola et al, 2022 ), effect size seemed to be affected by adherence: Patients with at least 4 of altogether 12 completed modules had an even bigger effect size ( d = 1.24). The robustness of the effect is supported by the effects on worry ( d = 0.47) and anxiety ( d = 0.38).…”
Section: Discussionsupporting
confidence: 73%
“…The exclusion criteria are suicidality, acute psychosis, serious personality disorder, and neurological or neuropsychiatric disorders that affect cognitive functioning. For a more detailed description of the treatment, see Ritola et al [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Internet-delivered cognitive behavioral therapy (iCBT) is an effective treatment for generalized anxiety disorder (GAD) [1][2][3][4]. Additionally, iCBT programs typically store data automatically, which is convenient in terms of computerized text analysis methods, or text mining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet-delivered treatment for GAD was effective for anxiety, worry, depression, functional impairment and quality of life [48,49]. A meta-analysis showed that internet-delivered cognitive behaviour therapy (ICBT) and face-to-face CBT created similar effects in treating anxiety disorders [50].…”
Section: Technology-delivered Therapymentioning
confidence: 99%